2018
DOI: 10.1002/admt.201800148
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Porous Piezoelectric Cantilever on a Pacemaker Lead for Compact Energy Harvesting

Abstract: ventricular dysrhythmias, and congestive heart failure. [1] Currently, lithium-based batteries provide the power for operations of implantable biomedical devices, such as cardiac pacemakers and AICD. Although the advances in microelectronics technology reduce the internal current drain concurrently allowing for a smaller volume and greater reliability of implantable biomedical devices, the batteries used in those devices only have a few years operating lifetime. Patients are still exposed to health risks assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 43 publications
0
29
0
Order By: Relevance
“…The maximum voltage of 1.5 V, current of 300 nA and power of 30 nW was obtained from 120 beats per minute with a blood pressure of 160/105 mmHg (Figure 27). They also, reported that the device can charge 1 mF capacitor to 1.0 V within 40 s. Furthermore, in 2019 Dong et al (2019) developed a unique design based on flexible porous P(VDF-TrFE) thin film within a dual-cantilever structure. This device is able to harvest energy from heart's motion by wrapping the device around the pacemaker lead with two free ends.…”
Section: Biomedical Devicesmentioning
confidence: 99%
See 2 more Smart Citations
“…The maximum voltage of 1.5 V, current of 300 nA and power of 30 nW was obtained from 120 beats per minute with a blood pressure of 160/105 mmHg (Figure 27). They also, reported that the device can charge 1 mF capacitor to 1.0 V within 40 s. Furthermore, in 2019 Dong et al (2019) developed a unique design based on flexible porous P(VDF-TrFE) thin film within a dual-cantilever structure. This device is able to harvest energy from heart's motion by wrapping the device around the pacemaker lead with two free ends.…”
Section: Biomedical Devicesmentioning
confidence: 99%
“…Gusarov et al (2016) fabricated a novel flexible thermal energy harvester using the coupled pyro/piezoelectric effect of PVDF with shape memory effect of NiTiCu alloy. The results showed that, the post-stamp size (27.5 mm 3 ) harvester can achieve an energy density of 0.41 mJ/cm 3 with a (Dong et al, 2019). temperature variation of 20°C (Figure 30).…”
Section: Flexible Hybrid Generatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finite Element Method (FEM) : The cantilever based energy harvesting structure had been widely explored in the literature to target low‐frequency vibrations. However, the bucked beam configuration showed significant advantages in integration, especially for compact energy harvesting application (i.e., the device was designed to be placed in the RV).…”
Section: Methodsmentioning
confidence: 99%
“…There is a lack of promising technologies that can efficiently covert the mechanical energy of the heart into electrical power without a thoracotomy and interfering with the cardiovascular functions. More recently, low profile, modular and compliant thin film energy harvesters were developed based on existing cardiac pacemaker leads, with minimal risk of interfering with the cardiovascular function [185,186]. The porous piezoelectric cantilever converted the kinetic energy of a pacemaker lead motion into an electrical power output [185], or a buckled beam array design was employed to utilize the bending of the lead of a cardiac pacemaker for generating electrical energy [187].…”
Section: Ultra-low Frequency In Vivo Sourcesmentioning
confidence: 99%